2010
DOI: 10.1186/1472-698x-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in the Iranian Blind War Survivors in 2007: a cross-sectional study

Abstract: BackgroundQuality of Life measurements are necessary tools for effectively evaluating health services. In the population of patients afflicted with war-related blindness in Iran, such measurements have yet to be documented and utilized. "The design and implementation of this study involved the determination of a baseline score for QOL in a population of Iranian blinded in the Iraq-Iran war in order to facilitate the design of interventions intended to improve the population's QOL."MethodsThis was a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 12 publications
1
28
1
2
Order By: Relevance
“…According to Larsson et al (17), the quality of life of amputees is likely to be improved by efforts at rehabilitation that are focused on improving mobility; an increase in physical activity and consequent reduction in physical limitations and dependencies can improve the quality of life. However, Amini et al (1) reported that psychological problems stand out as key influencers of quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Larsson et al (17), the quality of life of amputees is likely to be improved by efforts at rehabilitation that are focused on improving mobility; an increase in physical activity and consequent reduction in physical limitations and dependencies can improve the quality of life. However, Amini et al (1) reported that psychological problems stand out as key influencers of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The SF-36 is regarded as a generic tool for assessing quality of life, and it is not specific to subjects with lower limb amputation. However, many studies have used this tool to assess this population (1,16,19,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only the frequency and severity of diseases, but also the quality of life is an important aspect of one's health (WHO, 1997). Disability has a direct impact on quality of life (Edwards, 2003;Benitha&Tikly, 2007;Verbunt, 2008;Amini, 2010). Nearly every person may experience a temporary or permanent disability sometime in life, and this happens more often with advancing age.…”
Section: Introductionmentioning
confidence: 99%